An analysis of alcohol compression ignition strategies on different engine platforms - Brian Gainey; Benjamin Lawler; Ankur Bhatt; Kunal Vedpathak; Sebastian Verhelst; Quinten Dejaegere; Martin Tunér; Adam Dempsey; Jared Zeman; Tyler Johnston; Musharrat Chowdhury; Sanguk Lee; et al. (Fuel, 2026)

Chemogenetic inhibition of the anterior cingulate cortex increases safe decision-making in aged mice performing the Iowa Gambling Task - Benjamin Z. Roberts; M. Melissa Flesher; Landon F. Cunningham; Adam L. Halberstadt; Jared W. Young (Psychopharmacology, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

High-resolution surface and rootzone soil moisture over US cropland: A novel framework assimilating multi-source remote sensing data, machine learning, and the Layered Green and Ampt Infiltration with Redistribution model - Shuohao Cai; Yijia Xu; Zhengwei Yang; Wade T. Crow; Zhou Zhang; Jiali Shang; Jiangui Liu; Peter La Follette; Chris Reberg-Horton; Harry Schomberg; Steven Mirsky; Brian Davis; et al. (Remote Sensing of Environment, 2026)

A Proposed Novel Neurovascular Mechanism for Brain Network Dysfunction After Traumatic Injury - Taotao Wu; Jared A. Rifkin; Adam C. Rayfield; Keith A. Kroma-Wiley; Dani S. Bassett; David F. Meaney (Annals of Biomedical Engineering, 2026)
Current research in predicting traumatic brain injury risk focuses on the relationship between head impacts and the likelihood of white matter damage, often overlooking the role of neurovascular coupling in the injury response. To fill this gap, we combined biomechanical and neurodynamic principles to simulate alterations to large-scale resting-state brain activity following head impacts. We simulated cortical neural activity with a network of Kuramoto phase oscillators, using structural connectivity to define coupling and a vascular-informed local resource term to capture neurovascular coupling. By combining the neurodynamic model with a brain mechanics model, we investigated two mechanistic pathways of network dysfunction: (1) white matter damage, reflected in degrading network edges, and (2) local tissue oxygenation decline, reflected in adjusting the resource term at each network node. We simulated 53 real-world head impacts using a vasculature template to evaluate the changes in simulated functional connectivity (FC) and neural dynamics relative to injury outcomes (concussion vs. no concussion). To assess vascular variability, simulations were repeated across 41 individual vasculature maps. Our results show simulated FC changes (measured by Pearson’s correlation) consistently correlated well with injury outcomes, regardless of injury mechanism (AUC = 0.89 and 0.90), However, the two injury models yielded distinct FC patterns as indicated by graph metrics. Vascular variability substantially influenced how injury affected FC, with some brains exhibiting resilience to synchrony disruption depending on their vascular structure. These findings offer testable insight into the neurovascular mechanism of brain dysfunction after TBI and have important implications for individualized protection and treatment.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Use of light naphtha in heavy-duty compression ignition engines – Analysis of engine performance, emissions, and economics - Adam Dempsey; Jared Zeman; Musharrat Chowdhury; Tyler Johnston; Alexander Voice (Fuel, 2025)

The Impact of Climate Change on High‐Priority Areas of Conservation for Amphibians in North American Drylands - Jared E. Johnson; Heather L. Bateman; Adam Stein; Fábio Suzart de Albuquerque (Journal of Biogeography, 2025)
Aim The goals of this study were to (1) identify how climate change impacts the distribution of amphibian species and high‐priority conservation areas (HPCA) in the drylands of the Southwest United States and Northern Mexico, (2) describe the relationship between environmental variables and spatial configurations of HPCA and (3) explore how climate change will impact the distribution of HPCA and investigate the relationship between HPCA and protected area (PA) network. Location Southwest United States and Northern Mexico. Taxon Amphibians. Methods We used distribution maps for 209 amphibian species to estimate surrogates of amphibian diversity, assessed by rarity‐weighted richness (RWR), site importance (Zonation) and species richness. Then, we used species accumulation curves to assess their efficiency in representing amphibians in the least number of sites. Next, we used the most effective surrogate to identify HPCA for amphibians. We used environmental variables, usually related to amphibian distribution, and random forest models to assess the impact of climate on the spatial configuration of HPCA in the current and future times. We also used PA networks to assess their representation. Results RWR produced a similar spatial configuration of HPCA as Zonation but could not depict the same level of connectivity. HPCAs were observed mainly across California, central Texas and western Mexico. The spatial distribution of HPCA was mostly influenced by precipitation, temperature and solar radiation. Climate change will influence the future distribution of HPCA. The overlay between HPCA and PA is weak. Main Conclusion Climate change is becoming an ever‐increasing issue for conservation efforts, especially in dryland ecosystems where natural resources are already scarce for native species. Results show an alteration in the spatial configuration of amphibian HPCA, and much is still needed to protect and manage them.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Correction: Effective conservation and management of giraffe require adopting recent advances of their taxonomy - Arthur B. Muneza; Michael B. Brown; Stephanie Fennessy; Sara D. Ferguson; Rigardt Hoffman; Axel Janke; Nikolaos Kargopoulos; Adams K. Kipchumba; Klaus-Peter Koepfli; Courtney J. Marneweck; Alice Petzold; Jared A. Stabach; et al. (Biodiversity and Conservation, 2025)

Effective conservation and management of giraffe require adopting recent advances of their taxonomy - Arthur B. Muneza; Michael B. Brown; Stephanie Fennessy; Sara D. Ferguson; Rigardt Hoffman; Axel Janke; Nikolaos Kargopoulos; Adams K. Kipchumba; Klaus-Peter Koepfli; Courtney J. Marneweck; Alice Petzold; Jared A. Stabach; et al. (Biodiversity and Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Limited effects of thinning on laminated root rot induced tree mortality in Douglas-fir forests of the Pacific Northwest, USA - Shawn B. McMurtrey; David N. Showalter; Adam R. Carson; Michael McWilliams; (Irene) Blakey Lockman; Everett M. Hansen; Jared M. LeBoldus (Forest Ecology and Management, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Validation and standardization of SPE and HPLC-UV methods for simultaneous determination of legacy and insensitive munitions - Austin Scircle; Ashley Kimble; Jared Smith; Bobbi Stromer; Samuel Beal; Jay Clausen; Thomas Georgian; Adam Mumford; Geoffrey Giarmo; Martin Peterson; Hart Hedgpeth; Rebecca Crouch; et al. (Environmental Nanotechnology, Monitoring & Management, 2023)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

History of excess-light exposure modulates extent and kinetics of fast-acting non-photochemical energy dissipation - Barbara Demmig-Adams; Stephanie K. Polutchko; Jared J. Stewart; William W. Adams (Plant Physiology Reports, 2022)

Concussion Prone Scenarios: A Multi-Dimensional Exploration in Impact Directions, Brain Morphology, and Network Architectures Using Computational Models - Taotao Wu; Jared A. Rifkin; Adam C. Rayfield; Erin D. Anderson; Matthew B. Panzer; David F. Meaney (Annals of Biomedical Engineering, 2022)

Local groundwater decline exacerbates response of dryland riparian woodlands to climatic drought - Jared Williams; John C. Stella; Steven L. Voelker; Adam M. Lambert; Lissa M. Pelletier; John E. Drake; Jonathan M. Friedman; Dar A. Roberts; Michael Bliss Singer (Global Change Biology, 2022)
Dryland riparian woodlands are considered to be locally buffered from droughts by shallow and stable groundwater levels. However, climate change is causing more frequent and severe drought events, accompanied by warmer temperatures, collectively threatening the persistence of these groundwater dependent ecosystems through a combination of increasing evaporative demand and decreasing groundwater supply. We conducted a dendro‐isotopic analysis of radial growth and seasonal (semi‐annual) carbon isotope discrimination (Δ 13 C) to investigate the response of riparian cottonwood stands to the unprecedented California‐wide drought from 2012 to 2019, along the largest remaining free‐flowing river in Southern California. Our goals were to identify principal drivers and indicators of drought stress for dryland riparian woodlands, determine their thresholds of tolerance to hydroclimatic stressors, and ultimately assess their vulnerability to climate change. Riparian trees were highly responsive to drought conditions along the river, exhibiting suppressed growth and strong stomatal closure (inferred from reduced Δ 13 C) during peak drought years. However, patterns of radial growth and Δ 13 C were quite variable among sites that differed in climatic conditions and rate of groundwater decline. We show that the rate of groundwater decline, as opposed to climate factors, was the primary driver of site differences in drought stress, and trees showed greater sensitivity to temperature at sites subjected to faster groundwater decline. Across sites, higher correlation between radial growth and Δ 13 C for individual trees, and higher inter‐correlation of Δ 13 C among trees were indicative of greater drought stress. Trees showed a threshold of tolerance to groundwater decline at 0.5 m year −1 beyond which drought stress became increasingly evident and severe. For sites that exceeded this threshold, peak physiological stress occurred when total groundwater recession exceeded ~3 m. These findings indicate that drought‐induced groundwater decline associated with more extreme droughts is a primary threat to dryland riparian woodlands and increases their susceptibility to projected warmer temperatures.

Interspecific Competition is Prevalent and Stabilizes Plant Production in a Brackish Marsh Facing Sea Level Rise - Jared R. Gabriel; Jessica Reid; Le Wang; Thomas J. Mozdzer; Dennis F. Whigham; J. Patrick Megonigal; J. Adam Langley (Estuaries and Coasts, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Evidence for ephemeral ring species formation during the diversification history of western fence lizards ( Sceloporus occidentalis ) - Nassima M. Bouzid; James W. Archie; Roger A. Anderson; Jared A. Grummer; Adam D. Leaché (Molecular Ecology, 2022)
Divergence is often ephemeral, and populations that diverge in response to regional topographic and climatic factors may not remain reproductively isolated when they come into secondary contact. We investigated the geographical structure and evolutionary history of population divergence within Sceloporus occidentalis (western fence lizard), a habitat generalist with a broad distribution that spans the major biogeographical regions of Western North America. We used double digest RAD sequencing to infer population structure, phylogeny and demography. Population genetic structure is hierarchical and geographically structured with evidence for gene flow between biogeographical regions. Consistent with the isolation–expansion model of divergence during Quaternary glacial–interglacial cycles, gene flow and secondary contact are supported as important processes explaining the demographic histories of populations. Although populations may have diverged as they spread northward in a ring‐like manner around the Sierra Nevada and southern Cascade Ranges, there is strong evidence for gene flow among populations at the northern terminus of the ring. We propose the concept of an “ephemeral ring species” and contrast S . occidentalis with the classic North American ring species, Ensatina eschscholtzii . Contrary to expectations of lower genetic diversity at northern latitudes following post‐Quaternary‐glaciation expansion, the ephemeral nature of divergence in S . occidentalis has produced centres of high genetic diversity for different reasons in the south (long‐term stability) vs. the north (secondary contact).

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

High‐resolution dynamically downscaled rainfall and temperature projections for ecological life zones within Puerto Rico and for the U.S. Virgin Islands - Jared H. Bowden; Adam J. Terando; Vasu Misra; Adrienne Wootten; Amit Bhardwaj; Ryan Boyles; William Gould; Jaime A. Collazo; Tanya L. Spero (International Journal of Climatology, 2021)
The weather research and forecasting (WRF) model and a combination of the regional spectral model (RSM) and the Japanese Meteorological Agency Non‐Hydrostatic Model (NHM) were used to dynamically downscale selected CMIP5 global climate models to provide 2‐km projections with hourly model output for Puerto Rico and the U.S. Virgin Islands. Two 20‐year time slices were downscaled for historical (1986–2005) and future (2041–2060) periods following RCP8.5. Projected changes to mean and extreme temperature and precipitation were quantified for Holdridge life zones within Puerto Rico and for the U.S. Virgin Islands. The evaluation reveals a persistent cold bias for all islands in the U.S. Caribbean, a dry bias across Puerto Rico, and a wet bias on the windward side of mountains within the U.S. Virgin Islands. Despite these biases, model simulations show a robust drying pattern for all islands that is generally larger for Puerto Rico (25% annual rainfall reduction for some life zones) than the U.S. Virgin Islands (12% island average). The largest precipitation reductions are found during the more convectively active afternoon and evening hours. Within Puerto Rico, the model uncertainty increases for the wetter life zones, especially for precipitation. Across the life zones, both models project unprecedented maximum and minimum temperatures that may exceed 200 days annually above the historical baseline with only small changes to the frequency of extreme rainfall. By contrast, in the U.S. Virgin Islands, there is no consensus on the location of the largest drying relative to the windward and leeward side of the islands. However, the models project the largest increases in maximum temperature on the southern side of St. Croix and in higher elevations of St. Thomas and St. John.

Tryptophan degradation is associated with risk-taking propensity in methamphetamine users with treated HIV infection - Jared Lee; Ji-Young Lee; Christina S. Meade; Michael Cohn; Antonio Chahine; Samantha E. Dilworth; Jessica F. Magidson; Hetta Gouse; Dietmar Fuchs; Adam W. Carrico (Journal of NeuroVirology, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Perspective: Developing Flow Policies to Balance the Water Needs of Humans and Wetlands Requires a Landscape Scale Approach Inclusive of Future Scenarios and Multiple Timescales - Brent Murry; Jared Bowden; Benjamin Branoff; Miguel García-Bermúdez; Beth A. Middleton; Jorge R. Ortiz-Zayas; Carla Restrepo; Adam Terando (Wetlands, 2019)

Interaction between invasive plant leaf litter and NaCl on two model amphibians - Devin G. DiGiacopo; George A. Meindl; Sean Ryan; Jared Jaeger; Matthew Wersebe; Amelia Martin; Seth A. Robinson; Gabrielle Graham; Adam R. Palmer; Amanda Setteducate; Ian Murray; Kirsten Prior; et al. (Biological Invasions, 2019)

Root and mycorrhizal fungal foraging responses to fruit removal in apple trees - Emily K. Lavely; Jianghong Zhang; Thomas S. Adams; David R. Bryla; Jared L. DeForest; Richard P. Marini; Robert Crassweller; David M. Eissenstat (Plant and Soil, 2018)

Inhibition of the receptor for advanced glycation end-products (RAGE) protects from secondhand smoke (SHS)-induced intrauterine growth restriction IUGR in mice - Joshua B. Lewis; Camilo Mejia; Clinton Jordan; Troy D. Monson; Jared S. Bodine; Todd M. Dunaway; Kaleb M. Egbert; Adam L. Lewis; Tanner J. Wright; K. Connor Ogden; Dallin S. Broberg; Parker D. Hall; et al. (Cell and Tissue Research, 2017)

Acclimation of Swedish and Italian ecotypes of Arabidopsis thaliana to light intensity - Jared J. Stewart; Stephanie K. Polutchko; William W. Adams; Barbara Demmig-Adams (Photosynthesis Research, 2017)

Bayesian inference of species diffusion in the West African Agama agama species group (Reptilia, Agamidae) - Adam D. Leaché; Jared A. Grummer; Michael Miller; Sneha Krishnan; Matthew K. Fujita; Wolfgang Böhme; Andreas Schmitz; Matthew Lebreton; Ivan Ineich; Laurent Chirio; Caleb Ofori-boateng; Edem A. Eniang; et al. (Systematics and Biodiversity, 2017)

Do dams also stop frogs? Assessing population connectivity of coastal tailed frogs (Ascaphus truei) in the North Cascades National Park Service Complex - Jared A. Grummer; Adam D. Leaché (Conservation Genetics, 2017)

Inhibition of the multidrug efflux pump LmrS from Staphylococcus aureus by cumin spice Cuminum cyminum - Prathusha Kakarla; Jared Floyd; MunMun Mukherjee; Amith R. Devireddy; Madhuri A. Inupakutika; Indrika Ranweera; Ranjana KC; Ugina ‘Shrestha; Upender Rao Cheeti; Thomas Mark Willmon; Jaclyn Adams; Merissa Bruns; et al. (Archives of Microbiology, 2017)

Evidence for concerted movement of nuclear and mitochondrial clines in a lizard hybrid zone - Adam D. Leaché; Jared A. Grummer; Rebecca B. Harris; Ian K. Breckheimer (Molecular Ecology, 2017)
Moving hybrid zones provide compelling examples of evolution in action, yet long‐term studies that test the assumptions of hybrid zone stability are rare. Using replicated transect samples collected over a 10‐year interval from 2002 to 2012, we find evidence for concerted movement of genetic clines in a plateau fence lizard hybrid zone ( Sceloporus tristichus ) in Arizona. Cline‐fitting analyses of SNP and mt DNA data both provide evidence that the hybrid zone shifted northward by approximately 2 km during the 10‐year interval. For each sampling period, the mt DNA cline centre is displaced from the SNP cline centre and maintaining an introgression distance of approximately 3 km. The northward expansion of juniper trees into the Little Colorado River Basin in the early 1900s provides a plausible mechanism for hybrid zone formation and movement, and a broadscale quantification of recent land cover change provides support for increased woody species encroachment at the southern end of the hybrid zone. However, population processes can also contribute to hybrid zone movement, and the current stability of the ecotone habitats in the centre of the hybrid zone suggests that movement could decelerate in the future.

Premature responses in the five-choice serial reaction time task reflect rodents’ temporal strategies: evidence from no-light and pharmacological challenges - Zackary A. Cope; Adam L. Halberstadt; Jordy van Enkhuizen; Aaron D. Flynn; Michelle Breier; Neal R. Swerdlow; Mark A. Geyer; Jared W. Young (Psychopharmacology, 2016)

Mycorrhizal fungi and roots are complementary in foraging within nutrient patches - Lei Cheng; Weile Chen; Thomas S. Adams; Xing Wei; Le Li; Michael Luke McCormack; Jared L. DeForest; Roger T. Koide; David M. Eissenstat (Ecology, 2016)
The roots of the majority of tree species are associated with either arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi. The absorptive roots of tree species also vary widely in their diameter. The linkages between root thickness, mycorrhiza type and nutrient foraging are poorly understood. We conducted a large root ingrowth experiment in the field to investigate how absorptive roots of varying thickness and their associated fungi (AM vs. EM) exploit different nutrient patches (inorganic and organic) in a common garden. In nutrient‐rich patches, thin‐root tree species more effectively proliferated absorptive roots than thick‐root tree species, whereas thick‐root tree species proliferated more mycorrhizal fungal biomass than thin‐root tree species. Moreover, nutrient patches enriched with organic materials resulted in greater root and mycorrhizal fungal proliferation compared to those enriched with inorganic nutrients. Irrespective of root morphology, AM tree species had higher root foraging precision than mycorrhizal hyphae foraging precision within organic patches, whereas EM tree species exhibited the opposite. Our findings that roots and mycorrhizal fungi are complementary in foraging within nutrient patches provide new insights into species coexistence and element cycling in terrestrial ecosystems.

Differences in light-harvesting, acclimation to growth-light environment, and leaf structural development between Swedish and Italian ecotypes of Arabidopsis thaliana - Jared J. Stewart; William W. Adams; Christopher M. Cohu; Stephanie K. Polutchko; Elizabeth M. Lombardi; Barbara Demmig-Adams (Planta, 2015)

Endocrine response to acute resistance exercise in obese versus lean physically active men - Daniela A. Rubin; Hoang N. Pham; Eric S. Adams; Andrew R. Tutor; Anthony C. Hackney; Jared W. Coburn; Daniel A. Judelson (European Journal of Applied Physiology, 2015)

Estimating the temporal and spatial extent of gene flow among sympatric lizard populations (genus Sceloporus ) in the southern Mexican highlands - Jared A. Grummer; Martha L. Calderón‐Espinosa; Adrián Nieto‐Montes de Oca; Eric N. Smith; Fausto R. Méndez‐de la Cruz; Adam D. Leaché (Molecular Ecology, 2015)
Interspecific gene flow is pervasive throughout the tree of life. Although detecting gene flow between populations has been facilitated by new analytical approaches, determining the timing and geography of hybridization has remained difficult, particularly for historical gene flow. A geographically explicit phylogenetic approach is needed to determine the overlap of ancestral populations. In this study, we performed population genetic analyses, species delimitation, simulations and a recently developed approach of species tree diffusion to infer the phylogeographic history, timing and geographic extent of gene flow in lizards of the Sceloporus spinosus group. The two species in this group, S. spinosus and S. horridus , are distributed in eastern and western portions of Mexico, respectively, but populations of these species are sympatric in the southern Mexican highlands. We generated data consisting of three mitochondrial genes and eight nuclear loci for 148 and 68 individuals, respectively. We delimited six lineages in this group, but found strong evidence of mito‐nuclear discordance in sympatric populations of S. spinosus and S. horridus owing to mitochondrial introgression. We used coalescent simulations to differentiate ancestral gene flow from secondary contact, but found mixed support for these two models. Bayesian phylogeography indicated more than 60% range overlap between ancestral S. spinosus and S. horridus populations since the time of their divergence. Isolation–migration analyses, however, revealed near‐zero levels of gene flow between these ancestral populations. Interpreting results from both simulations and empirical data indicate that despite a long history of sympatry among these two species, gene flow in this group has only recently occurred.

A global land-cover validation data set, part I: fundamental design principles - Pontus Olofsson; Stephen V. Stehman; Curtis E. Woodcock; Damien Sulla-Menashe; Adam M. Sibley; Jared D. Newell; Mark A. Friedl; Martin Herold (International Journal of Remote Sensing, 2012)

Human Dimensions - Bob Tjaden; Marissa Jo Daniel; Francisco Aguilar; Hank Stelzer; Timothy Gallaher; John Kushla; James Henderson; Andrew Londo; Melissa Kreye; Damian Adams; Tatiana Borisova; Francisco Escobedo; et al. (Journal of Forestry, 2011)
12The University of MD Extension (UME) has been very effective in teaching forest landowners concepts and principles of forest management through seminars, workshops and field days. After evaluating these techniques and recognizing people learn differently, new delivery methods were developed. UME developed a landowner based forestry correspondence course in two formats, first a traditional paper then a web based version. These were developed to support the range of ages, learning styles, high-speed internet availability and computer knowledge. Both versions lead the learner through the components of a forest stewardship plan. Upon course completion, the student has the framework of a forest stewardship plan in a format acceptable for State Forester approval. This has helped the State Forester meet forest stewardship plan goals during a significant decline of personnel who normally assist forest landowners. The courses have also helped forest landowners meet the NRCS requirements of having a plan in order to qualify for certain federal cost share programs. We are constantly adapting the courses based on course evaluations, new issues and programs, and innovative forest management techniques. Evaluations are performed upon the completion of the course to assist in measuring overall course effectiveness, student success, plan objectives and any enhancements necessary to improve the course. There is also a follow-up evaluation performed five years after completion to evaluate plan implementation, behavioral changes, knowledge maintained, acres impacted, financial impacts, and direct contacts of the students. Data from all evaluations will be presented in the poster as well as lesson learned.